Projek Penguatan Profil Pelajar Pancasila Terhadap Sikap Mandiri Siswa SMP Negeri 35 Bekasi - Putri Rinjani Lestari; Supriyadi; Eka Putri (INDO PUBLISHING, 2025)
This research aims to determine the effect of the Pancasila Student Profile Strengthening Project (P5) on students’ independence at SMP Negeri 35 Bekasi. The study employed a quantitative approach with an associative research design. The population consisted of 317 eighth-grade students, while the sample of 147 students was selected using a simple random sampling technique. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data analysis was carried out using simple linear regression with SPSS version 20. The results showed that the significance value was 0.000 < 0.05, indicating that the alternative hypothesis (Ha) was accepted while the null hypothesis (H0) was rejected. This proves that there is a positive and significant effect of the Pancasila Student Profile Strengthening Project (P5) on students’ independence. Thus, the better the implementation of P5, the higher the level of student independence. This study emphasizes the importance of P5 in fostering students’ independence to build a generation that is characterized, self-reliant, and ready to face future challenges.